Altered gut microbiome composition in nontreated plaque psoriasis patients. (February 2023) - Wen, Chunmiao; Pan, Yuanming; Gao, Ming; Wang, Jianlei; Huang, Kun; Tu, Ping
Abstract: Recent studies have demonstrated that dysbiosis of the gut microbiota is associated with psoriasis, but these studies showed some conflicting results. Our study examined differences in microbiome composition associated in people with psoriasis and those without. Comparing individuals with their healthy partners was a second strategy. We explored the fecal microbiota among 32 nontreated plaque psoriasis patients, 15 healthy controls and 17 healthy couples by metagenomic gene sequencing. The relative levels of intestinal microbiota of the psoriasis cohort differed from those in healthy controls and these patients' partners. However, there was no microbial diversity among these three cohorts. On the level of the phylum, Firmicutes and Bacteroidetes ' relative abundances were reversed. Escherichia coli was significantly enriched in the psoriasis group compared with the healthy people and the healthy spouses. Gene functional analysis indicated that Ribosome (ko03010) was upregulated, Flagellar assembly (ko02040) and Bacterial chemotaxis (ko02030) were downregulated in the psoriasis cohort compared with the healthy individuals and the healthy spouses. The microbiota in severe psoriasis patients differed from those with milder conditions. These findings strongly support the association between intestinal flora and psoriasis. It is necessary to perform more meaningful experiments to identify whether the differences of gut microbiota are the cause or consequences of psoriasis in future. Highlights: None of the participants had taken any medication for 6 months before the study began. We explored patients and their healthy spouses as subgroups. Escherichia coli was significantly enriched in the psoriasis group compared with the healthy people and the healthy spouses. These findings strongly support the association between intestinal flora and psoriasis.